Model-Based Methodologies for Pervasive and Embedded Software 8th International Workshop, MOMPES 2012, Essen, Germany, September 4, 2012. Revised Papers - Machado, Ricardo J.; Maciel, Rita Suzana P.; Rubin, Julia; Botterweck, Goetz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Workshop on Model-Based Methodologies for Pervasive and Embedded Software, MOMPES 2012, held in Essen, Germany, in September 2012. The 7 revised full papers presented together with 1 short papers were carefully reviewed and selected from 16 submissions. The papers cover a large spectrum of topics including model-driven engineering, model analysis, runtime verification, modeling of reactive systems, variability modeling, and domain-specific languages.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer simulation; Computer Science; Software Engineering; Logics and Meanings of Programs; Computer Communication Networks; Programming Languages, Compilers, Interpreters; Artificial Intelligence (incl. Robotics).; Simulation and Modeling